A review on emerging pharmaceutical residues in Ethiopia: occurrence, ecotoxicological aspects, and regulatory concerns - Tegegne, Addisu Afrassa; Mekasha, Yesuneh Tefera; Ayu, Adugna Abera; Hasen, Gemmechu; Suleman, Sultan (Frontiers in Microbiology, 2024)
BackgroundPharmaceuticals are expected to improve human and animal health, but improper management and regulation have led to adverse effects such as reproductive disorders, antibiotic resistance, and biodiversity loss in ecosystems. Their presence in the environment poses significant risks, including a reduction in biodiversity, reproductive issues, and the development of antimicrobial resistance. This review aims to examine the occurrence and sources of pharmaceuticals in the environment and their ecotoxicological and regulatory aspects, with a focus on Ethiopia.MethodsA narrative review of relevant studies conducted in Ethiopia was undertaken. The review included findings on the occurrence, sources, contributing factors, ecotoxicological impacts, and regulatory concerns related to pharmaceutical residues in the environment. Literature was sourced from Google Scholar, Scopus, PubMed, and institutional repositories.ResultThe findings revealed the detection of pharmaceutical residues in wastewater treatment facilities, aquatic environments (e.g., lakes and rivers), and commercially available animal products. Aquatic samples also showed significant concentrations, with sulfamethoxazole and fluconazole detected at 0.15 μg/L and 0.012 μg/L, respectively. Antimicrobial resistance genes were identified in wastewater and treatment plant samples, which correlate with the presence of pharmaceutical residues. An ecological risk assessment based on the risk quotient (RQ) revealed ciprofloxacin as a major concern, with an RQ of 8.58, indicating high ecological risk. Sulfonamides exhibited moderate risk, with RQ values ranging from 0.1 to 1.ConclusionThe study highlights the significant presence of pharmaceutical residues in the environment and underscores the inadequacy of regulatory enforcement in addressing this public health issue. Urgent measures are required to prevent environmental contamination and mitigate public health risks, including antimicrobial resistance. Strengthened regulatory measures and proactive interventions by relevant organizations are essential to control and prevent pharmaceutical residues in the environment, offering a critical solution for the country.